Pengaruh Laba Kotor, Laba Operasi, Laba Bersih, Perubahan Piutang, Perubahan Hutang Dan Perubahan Persediaan Dalam Memprediksi Arus Kas Di Masa Mendatang (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Putri Widi Astuti; Dwika Lodia Putri; Aljufri (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to determine the effect of gross profit, operating profit, net income, changes in receivables, changes in payables and changes in inventory in predicting future cash flows (empirical studies on mining companies listed on the Indonesia Stock Exchange in 2016-2020). The population in this study are all mining companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The total population in this study were 47 mining companies.The sampling technique used purposive sampling method which resulted in 12 companies as samples. The results showed that gross profit, operating profit, net income, changes in debt, and changes in inventory had an effect on predicting future cash flows, while changes in accounts receivable had no effect on predicting future cash flows. Then there is the effect of gross profit, operating profit, net profit, changes in receivables, changes in debt and changes in inventory in predicting future cash flows simultaneously.